RESPONSE OF BOARDING SCHOOLS TO COVID-19: Dynamics and Theological Struggles of Boarding Schools in Mandailing Natal - Rohman Rohman; Muhammad Irsan Barus; Torkis Lubis (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
The study of Islamic boarding schools has its dynamics and uniqueness. As an Islamic educational institution, the response of Islamic boarding schools to the issue of Covid-19 has had a sizable social impact in shaping the mindset and religious actions of the surrounding community. This study reveals the dynamics and theological struggles within Islamic boarding schools in response to the policy of handling Covid-19 in Mandailing Natal. This study uses a qualitative descriptive approach, the data informants are residents of Islamic boarding schools consisting of leaders, clerics, students, and the community around the Islamic boarding school. The results of this study found that there were three styles of thinking in each Islamic boarding school in response to the handling of Covid-19, namely conservative, semi-conservative, and non-conservative. In general, Islamic boarding schools accept government policies in dealing with Covid-19, but in practice, Islamic boarding schools tend to ignore the rules. The clerics who are pro in handling Covid-19, provide theological enlightenment to the students and the surrounding community. On the other hand, the clerics who are resistant to handling Covid-19, give the view that Covid-19 is a game by the political elite in government. However, in this case, the resistant kyai did not provoke the students and the community.